2005
DOI: 10.1081/fst-200050697
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Hydrogen, Helium and Their Mixtures on the Synthesis of Carbon Nanotubes in a DC Arc‐Discharger

Abstract: Multiwalled carbon nanotubes (MWCNTs) have been produced with a DC arc-discharger in the presence of hydrogen, helium or hydrogen-helium mixtures using high gas pressures (60 kPa-140 kPa) and varying gas pressure ratios (10%-100% hydrogen in helium at 100 kPa). Variation of He pressure hardly affected the cathode deposit formation while increased H 2 pressure resulted in an increase in chamber soot and cathode material formation but a relative decrease in the % MWCNT production. Varying H 2 /He gas ratios at a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 31 publications
(34 reference statements)
0
1
0
Order By: Relevance
“…As carbon nanotubes show a cylindrical shape, research efforts have concentrated on the possibility of controlling alignment, diameters, and lengths , so that many theoretical and experimental studies on these topics have been reported. , Classical and path integral molecular simulations were used to study the physisorption of hydrogen, helium, neon, nitrogen, argon, and methane in cylindrical pores, SWCNTs, and bundles of SWCNT for a range of pressures, temperatures, tube radii, and bundle structures . There is currently a considerable interest in the functionalization of carbon nanotubes, one motivation being to increase their very low solubility in both aqueous and organic solvents .…”
Section: Introductionmentioning
confidence: 99%
“…As carbon nanotubes show a cylindrical shape, research efforts have concentrated on the possibility of controlling alignment, diameters, and lengths , so that many theoretical and experimental studies on these topics have been reported. , Classical and path integral molecular simulations were used to study the physisorption of hydrogen, helium, neon, nitrogen, argon, and methane in cylindrical pores, SWCNTs, and bundles of SWCNT for a range of pressures, temperatures, tube radii, and bundle structures . There is currently a considerable interest in the functionalization of carbon nanotubes, one motivation being to increase their very low solubility in both aqueous and organic solvents .…”
Section: Introductionmentioning
confidence: 99%